Recurrent bilateral gestational gigantomastia after reduction mammoplasty: A case report and review of the literature - Alasi, Mustapha Adeyinka; Faniyi, Adebayo Olabisi (Indian Journal of Case Reports, 2025)
Gestational gigantomastia (GG) is a benign condition characterized by excessive breast enlargement during pregnancy, which can lead to significant physical and psychosocial distress. We present a 22-year-old woman who experienced progressive bilateral breast enlargement for 20 weeks. She was G3P1+1 A1, with her last menstrual period being 28 weeks prior. The patient had experienced similar breast enlargement during her last pregnancy, which was treated with bilateral reduction mammoplasty. Upon examination, both breasts were disproportionately enlarged with no nipple-areolar complex. Initially, she was treated with oral bromocriptine 5 mg daily, which reduced the enlargement. However, her condition worsened in the immediate post-partum period, resulting in significant breast enlargement, deformity, pain, spontaneous ulceration, and tissue necrosis. Ultimately, she underwent a bilateral simple mastectomy. GG is a rare condition that can severely impact a woman’s quality of life. The previous occurrence of GG increases the likelihood of recurrence in subsequent pregnancies.